2023
DOI: 10.1111/sum.12892
|View full text |Cite
|
Sign up to set email alerts
|

Organic residues and their impact on soil health, crop production and sustainable agriculture: A review including bibliographic analysis

Abstract: Despite their potential as a sustainable source of soil nutrients and organic matter, waste organic residues are often discarded rather than utilized in agriculture. This review examines the current state‐of‐the‐art in the application of organic residues in agricultural production systems by analysing trends and results in published research conducted on their use for soil health and crop production purposes. For this, a bibliographic analysis was conducted on 81 papers collected from the Web of Science databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 133 publications
0
5
0
Order By: Relevance
“…The study conducted at a public open space (near West Leederville Community Garden and Earthwise Community Garden) which is a historical soil contamination site also showed no significant heavy metal pollution (Andrew, 2021). The Zn, Cu, Pd and Cd content in raised beds is higher than in the control plots, probably because compost applied to the gardening area has a high concentration of metals (Bolan, Adriano, & Mahimairaja, 2004; Brichi et al., 2023). Studies have found that the application of compost (where heavy metals are present) can increase heavy metal concentrations in soil because of accumulation processes impacting soil quality (Bolan et al., 2014; Pinamonti et al., 1997, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The study conducted at a public open space (near West Leederville Community Garden and Earthwise Community Garden) which is a historical soil contamination site also showed no significant heavy metal pollution (Andrew, 2021). The Zn, Cu, Pd and Cd content in raised beds is higher than in the control plots, probably because compost applied to the gardening area has a high concentration of metals (Bolan, Adriano, & Mahimairaja, 2004; Brichi et al., 2023). Studies have found that the application of compost (where heavy metals are present) can increase heavy metal concentrations in soil because of accumulation processes impacting soil quality (Bolan et al., 2014; Pinamonti et al., 1997, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, along with diversified cover crops, the inclusion of organic residues such as cattle manure and organic compost can Brazilian Archives of Biology and Technology. Vol.67(spe1): e24230789, 2024 www.scielo.br/babt contribute positively to the maintenance of soil pH and improvements of macronutrient availability [52] in all tillage practices. Furthermore, we highlight that soil in all tillage practices and SF was functioning close to the maximum potential of physical and biological capacity.…”
Section: Soil Health Response To Soil Tillage In Campos Gerais Regionmentioning
confidence: 99%
“…Given the scarcity of extant research pertaining to the residual effects of varying organic and inorganic fertilizer levels on sesame crops subsequent to maize cultivation (Brichi et al., 2023; P. Singh et al., 2023), our current study assumes a pivotal role in ameliorating this lacuna. Our research is anchored in the pursuit of a quantitative appraisal of soil attributes, thereby poised to find the optimal blend of INM practices.…”
Section: Introductionmentioning
confidence: 99%